Application of Didactic Methods in Planting Values of Culture Through Maligya Ceremony at Hindu Communities - Santipatni, Gusti Ayu (Journal of Education Reseach and Evaluation, 2021)
The maligya ceremony is an implementation of Hinduism that involves Balinese cultural practices in Lombok. This study aims to study the application of didactic methods in cultivating cultural values through the maligya ceremony at the research location. The focus of this research is on the application of didactic methods in instilling cultural values through the maligya ceremony. This research method is qualitative interpretive with a case study approach. The results of the data analysis found three new findings. First, the dimension of introducing cultural values in religious practice as a cognitive aspect in the implementation of the maligya ceremony involves an aspect of awareness for lifelong learning. Second, the dimensions of the appreciation of cultural values in the maligya ceremony as the implementation of the affective aspects related to the awareness to respect the cultural values of ancestral heritage. Third, the dimension of practicing cultural values in the practice of the maligya ceremony is related to the realization of a sense of devotion before the ancestors and the preservation of cultural values as a means of improving the quality of life of the Hindu community who performs it. Based on the results of this study, it can be concluded that the didactic method is an effective strategy in instilling cultural values in the implementation of Hinduism through the maligya ceremony.